Divisia monetary aggregate and monetary transmission mechanism in the Democratic Republic of Congo (DRC). Issue 4 (23rd February 2020) - Yemba, B.P.; Tang, B.; Kitenge, E; Nsumbu, J.
ABSTRACT: While the majority on the effectiveness of monetary policies focus on either interest or money channels, we analyze the effectiveness of a composite monetary instrument: The Divisia Aggregate Index (DMAI). Dynamic effects of the DMAI on other economic factors is analyzed through the Factor Augmented Vector Autoregressive model (FAVAR). The latter address the potential arbitrary selection of variables to incorporate in a standard VAR model, and is built from the ability of factor analysis to summarize a very high number of variables into few factors. The FAVAR is applied to monthly data  over the period 01:1996-12:2017 from the Democratic Republic of the Congo. Our empirical results reveal that the DMAI outperforms other monetary policy instruments that use separately interest or money channels, in boosting output and triggering price stability.